Association analysis of two polymorphisms in neuregulin-1 gene in a Turkish schizophrenia sample (Annals of Medical Research, 2022)
Aim: NRG1 is one of the genes that was reported to have susceptibility alleles effecting the phenotype of schizophrenia. There are many SNPs (single nucleotide polymorphisms) located in the NRG1 gene with suspected alleles which were associated to schizophrenia. In this study, we investigated the potential associations between schizophrenia and NRG1 polymorphisms rs4560751 and rs3802160.Materials and Methods: We collected DNA samples of 96 patients diagnosed for schizophrenia and 100 healthy controls living in Malatya-Turkey. We genotyped two NRG1 SNPs mentioned above and compared case and control groups for distributions of alleles and genotypes. We also tested the potential associations in dominant models. We used Chi-Squared test for hypothesis testing.Results: No significant differences were seen between the groups of patients and controls for the distributions of alleles and genotypes of two NRG1 SNPs we have screened.Conclusion: The results of our experiments and statistical tests we have done indicated that in the population we have screened there was no sufficient evidence to support the association of NRG1 SNPs rs4560751 and rs3802160 with schizophrenia.
Keywords: Schizophrenia; Genetics; Association; Neuregulin 1; Polymorphism; Turkey